EVALUASI SARANA DAN PRASARANA PEMBELAJARAN JURUSAN TEKNIK KOMPUTER JARINGAN MENGGUNAKAN MODEL CIPP DI SMK Negeri 2 PAYAKUMBUH - Rahmi Oktarina (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2016)
This article was a study about the implementation of the learning facilities and infratructures in SMKN 2 Payakumbuh in its relationship to the prior low achievement of students in some courses in Computer Network Engineering department. Evaluation method used was the context, input, process, and product (CIPP) that included in a mixed method research. Sources of qualitative data obtained from the vice headmaster of facilities and infrastructure of SMKN 2 Payakumbuh, head of Computer Network Engineering department, head of the Computer Network Engineering lab and the teachers in that department.. The quantitative data were taken from students in XI TKJ class that consisted of 32 people. The research indicated that context component is in adequate category (73.71%); the Input component is in adequate category (76.79%); theProcess component is in adequate category (78.06%) and the Product component is also in adequate category (79.58%). Due to all of components were in adequate category, it was suggested to conduct the appropriate improvement to improve the students achievements in thoses Computer Network Engineering courses.